Effect of Electrode Material on Surface Roughness and Hardness of Jaw Implants - Yani Kurniawan; Nurdiana Mulyadi; Bambang Sulaksono (Politeknik Sukabumi, 2026)
Long processing time and decreased material hardness are the main problems in developing jaw implants using the EDM die-sinking method. Therefore, research is needed to speed up the process and minimize the decrease in hardness of jaw implant materials made using EDM die-sinking. This study aims to investigate the right type of electrode material to speed up the process time and minimize the decrease in hardness of jaw implant materials made using EDM die-sinking. The effect of electrode material in the manufacture of jaw implants was also investigated. The manufacture of jaw implants used copper, tungsten, brass, and high-speed steel (HSS) electrode materials. Pulse current and pulse on time used 6 A and 22 μs, respectively. The results showed that the surface roughness and decrease in hardness of jaw implant materials were influenced by the thermal conductivity of the electrode material. The best electrode material in the manufacture of jaw implants using EDM die-sinking is copper. The manufacturing process of jaw implants with copper material was approximately 7.5 hours. The surface roughness and hardness of jaw implants were approximately 1.97 μm and 150 HV, respectively.